2017
DOI: 10.1111/ecc.12796
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and healthcare utilisation near the end of life in patients with cancer

Abstract: The quality of medical care delivered to patients with cancer near the end of life is a significant issue. Previous studies have defined several areas suggestive of aggressive cancer treatment as potentially representing poor quality care. The primary objective of current analysis was to examine chemotherapy and healthcare utilisation in the last 3 months of life among patients with cancer that received palliative chemotherapy. Patients were selected from the hospital administration database of the Diakonessen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…It is a complex decision-making process that involves patient, family, oncologist and other members of the cancer care team. Chemotherapy at the end of life could decrease survival and increase health care utilization according to some studies (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex decision-making process that involves patient, family, oncologist and other members of the cancer care team. Chemotherapy at the end of life could decrease survival and increase health care utilization according to some studies (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…1,28,29 Because of oncologists' inaccurate predictions and optimistic viewpoints, patients may inappropriately receive cancer treatment close to death, as demonstrated in our study, which may influence inpatient mortality, EOL care, and health care spending and utilization. [30][31][32] However, the time between therapy discontinuation and death remains an imperfect metric of aggressive or appropriate care as patients may die of completely unrelated causes. Cancer treatment, insofar as it remains safe to administer, may still help alleviate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017 in the Netherlands, 59% of cancer patients were admitted to the hospital in the last 3 months of life, and 27% visited the ER in the last month of life [46,47]. Other studies, not limited to patients with brain metastases, reported 30 to 74% of patients visiting the ER and 41 to 55% being admitted in the last 3 months of life [33,[48][49][50]. We observed that neurological symptoms were most often the reason for ER visits and hospitalization.…”
Section: Discussionmentioning
confidence: 99%